2012
DOI: 10.1519/jsc.0b013e31821d9789
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Whole-Body Vibration on Neuromuscular Responses in Older Individuals: Implications for Prescription of Vibratory Stimulation

Abstract: The aim of this study was to analyze surface electromyography activity (sEMG) and rating of perceived exertion (RPE) responses in different muscles while standing on a vibrating platform producing oscillations of different frequencies and amplitudes. Twenty community-dwelling older adults (79.6 ± 3.2 years) took part in the research. Subjects were exposed to 12 different vibration treatments of 15 seconds separated by 1 minute of rest in random order to check the influence of frequency (25, 35, and 45 Hz) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…The search for a dose-response relationship between the intensity of the vibration stimulation (i.e., vibration frequency and amplitude) and the induced effect on postural control has not been examined in other studies. However, other authors have corroborated the findings of this study and have reported the absence of a dose-response relationship among vibration stimulation intensity, the optimization of neuromuscular activation, and explosive strength [ 30 32 ]. Based on the previous literature and the results of the present study, no consensus exists regarding the occurrence of the residual acute effects induced by WBV on postural control.…”
Section: Resultssupporting
confidence: 88%
“…The search for a dose-response relationship between the intensity of the vibration stimulation (i.e., vibration frequency and amplitude) and the induced effect on postural control has not been examined in other studies. However, other authors have corroborated the findings of this study and have reported the absence of a dose-response relationship among vibration stimulation intensity, the optimization of neuromuscular activation, and explosive strength [ 30 32 ]. Based on the previous literature and the results of the present study, no consensus exists regarding the occurrence of the residual acute effects induced by WBV on postural control.…”
Section: Resultssupporting
confidence: 88%
“…The widest foot position of 23.3 cm from the central axis of the platform corresponded to an amplitude of 4 mm, as evaluated by double integration of the platform acceleration signal. As responses in sEMG activity are positively correlated to the vertical platform acceleration [22], the highest possible frequency-amplitude combination was chosen within the constraints of the WBV platform, which corresponded to 16 Hz and 4 mm. Although a vibration frequency of 16 Hz is rather low compared to those used in previous studies [1,27,30,31], significant increases in sEMG were reported for the same platform type with a lower frequency-amplitude combination [11].…”
Section: Wbv Exercisesmentioning
confidence: 99%
“…Increases on sEMGrms for lower limb muscles of older populations when compared to young individuals were prominent [50,51]. The authors relate the lower strength of old adults to the higher activation while standing on the functioning VP, as an attempt of adaptation, which may further improve stability and muscle power [26].…”
Section: Discussionmentioning
confidence: 92%
“…A sample size calculation (ß = 0.10) based on detecting a minimum of 20% of difference in sEMGrms of vastus lateralis (VL) (SD = 10) between the interventions, showed that at a 5% significance level would require a sample of 5 participants in groups with a power of 90% [26].…”
Section: Methodsmentioning
confidence: 99%